Komunikasi Pemasaran Objek Wisata Selabintana Sukabumi Dalam Membangun Brand Awareness - Moch Dafa Fadillah (STISIP Widyapuri Mandiri Sukabumi, 2025)
There is a phenomenon where the more the era develops, the more competitors there are in the tourism sector. Selabintana is a Sukabumi tourist spot that has been established for a long time since the Dutch colonial era until now. Currently, there are many competitors competing to develop their products, but Selabintana is not inferior to the development of the era, with that the researcher is interested in how the Selabintana tourist spot continues to maintain and develop the products they offer to the public. The objectives of this study are (1) To determine advertising in marketing communications of Selabintana Sukabumi tourist attractions in building Brand Awareness, (2) To determine sales promotion in marketing communications of Selabintana Sukabumi tourist attractions in building Brand Awareness, (3) To determine public relations in marketing communications of Selabintana Sukabumi tourist attractions in building Brand Awareness, (4) To determine personal sales in marketing communications of Selabintana Sukabumi tourist attractions in building Brand Awareness, (5) To determine production identity in marketing communications of Selabintana Sukabumi tourist attractions in building Brand Awareness. The theory used in this study is the marketing communication theory put forward by Octaviani (2023: 33- 34) including, Advertising, Sales Promotion, Public Relations, Personal Selling and Production Identity. This study uses a qualitative approach and descriptive method, with the Purposive Sampling technique. The equipment used in this study was a camera, notebook, tape recorder, and interview guidelines. Data collection techniques through observation, interviews and documentation. The subjects of this study were 4 people, namely 1 Room Division Manager, 1 Sales & Marketing Manager, and 2 Selabintana Sukabumi Tourist Visitors. The results of this study indicate that the Marketing Communication of Selabintana Sukabumi Tourist Attractions in Building Brand Awareness, namely Advertising has been running optimally, sales promotions have been running well, public relations have been widely covered, personal sales have not been running effectively, and production identity has been quite satisfacto